Agricultural Strategies of Young Farmers on Small-Scale Land in Sriharjo, Bantul - Dewi, Hani Puspita; Eddyono, Suzanna (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: The agricultural situation in the Special Region of Yogyakarta is becoming increasingly concerning. The number of farmers is declining, and young people are showing less interest in agriculture. This has led to problems with production output and a food security crisis. A solution to these challenges is to empower youth to engage in farming. The aim of this study is to identify groups of young farmers and the efforts made to address current challenges. The unit of analysis in this study is youth groups involved in farming activities on limited land. The research was conducted with a youth farming group called Taruna Tani Hijaunya Cinta in Sriharjo Village, Bantul. A case study design was employed, using in-depth interviews conducted both in person and via telephone. The research was carried out from January to June 2022, with limited observations and interviews due to the COVID-19 pandemic. To supplement the data, document and photo collection from the farmer group was also conducted. Thematic analysis was used to analyze various data sources. The findings of this study indicate that the majority of the group's members are children of farmers aged 17-35, with educational backgrounds ranging from secondary school to university students. The results show that the use of technology in farming, the development of social media for marketing, and the creation of agro-tourism have enhanced the competitiveness of young people in the agricultural sector, created new business opportunities, and stimulated local economic growth. For long-term sustainability, it is recommended that the government and educational institutions strengthen training and education programs for youth to enable them to continue innovating and adapting to market changes. Keywords: Limited Land Agriculture, Young Farmers, Youth